THU0188 Efficacy and safety of tofacitinib in patients with rheumatoid arthritis who did not respond to synthetic and biological dmards in clinical practice. (15th June 2017) - Luchikhina, EL; Karateev, D; Misiyuk, A; Demidova, N; Loukina, G; Abdulganieva, D; Baranov, A; Babaeva, A; Evstigneeva, L; Ivanova, O; Mazurov, V; Semagina, O; et al.
Abstract : Background: Tofacitinib (TOFA) is so far the only representative of a new class of Jak-kinase inhibitors in rheumatology. Despite extensive data on TOFA obtained from 3rd phase studies, for use in clinical practice, the information is limited. Objectives: To study the efficacy and safety of TOFA in RA in clinical practice. Methods: We represent the combined data from two parallel IV Phase open-label observational clinical trials, modelling clinical practice, conducted by very similar protocols in 11 rheumatology centers in Russia. Inclusion criteria were active RA, methotrexate (MTX) failure, and/or other synthetic or biologic DMARDs failure. In total, 142 pts (26 males, 116 females, age 51, 5±12, 2 years, disease duration 88, 6±78, 1 months, 86, 6% RF(+), 76, 6% ACPA(+), 81, 7% with erosive disease, DAS28-ESR 5, 89±1, 03, SDAI 35, 7±13, 4, HAQ 1, 59±0, 64) were included. 32 (22, 5%) pts had biologics in history. TOFA used in the dose of 5 mg BID for 6 months, with possibility to increase to 10 mg BID (carried out in 27 pts after 11, 3±2, 7 weeks). 115 (81%) pts received TOFA in combination with MTX (18±4, 5 mg per week), 18 with leflunomide or sulfasalazine, 9 pts used TOFA in monotherapy. Results: 129 (90, 8%) pts successfully completed the six-month period of treatment. TOFA was withdrawn due to lack of response in 6 cases, adverse events (AEs) in 4 (pneumonia, arterial hypertension, skin vasculitis, mouth ulcers), withdrawal of informed consent – 2, protocol violation – 1. At month 3 SDAI score decreased to 14, 6±10, 9 (p<0, 01), 55 (42, 6%) pts achieved SDAI LDA and 22 (17, 1%) SDAI remission; HAQ decreased to 0, 95±0, 61, HAQ≤0, 5 observed in 36 (27, 9%) pts. After 6 months, SDAI and HAQ scores decreased to 10, 5±8, 6 and 0, 83±0, 64 resp. (p<0, 01); 81 (62, 8%) pts achieved SDAI LDA and 29 (22, 5%) SDAI remission; HAQ≤0, 5 observed in 48 (37, 2%) pts. Results of treatment in patients with and without biological DMARDs in history were similar. Pts who needed dose escalation of TOFA had worse results at month 3 compared to others (SDAI 21±10, 2 and to 13, 2±10, 7 resp., p=0, 02), but after increase of the dose to 10 mg BID at month 6 they showed a slightly better result (SDAI 9, 5±7, 1 and to 10, 7±8, 9 resp., p=0, 54). Only 2 serious AEs (pneumonia and skin vasculitis) observed. We didn't see any case of Herpes zoster in our group. Conclusions: TOFA was effective in patients with severe RA who did not respond to both synthetic and biological DMARDs (achievement of SDAI LDA in 42, 6% of pts at month 3 and in 62, 8% at month 6). Dose escalation to 10 mg BID can be useful in ¼ of patients who do not respond to standard dose of TOFA. TOFA has shown a good safety profile. Acknowledgements: This scientific study was supported by grant by Pfizer. Disclosure of Interest: E. Luchikhina Grant/research support from: Pfizer, Biocad, Speakers bureau: Abbvie, Pfizer, Tirupharm, D. Karateev Grant/research support from: Pfizer, Consultant for: Pfizer, Tirupharm, Biocad, Egis, R-Pharm, Novartis, Speakers bureau: Abbvie, Bristol Myers Squibb, Pfizer, Roche, Tirupharm, Biocad, R-Pharm, Novartis, Egis, MSD, UCB, A. Misiyuk: None declared, N. Demidova: None declared, G. Loukina: None declared, D. Abdulganieva: None declared, A. Baranov: None declared, A. Babaeva: None declared, L. Evstigneeva: None declared, O. Ivanova: None declared, V. Mazurov: None declared, O. Semagina: None declared, A. Sizikov: None declared, V. Sorotskaya: None declared, E. Nasonov: None declared